Augmented reality interventions in oral health promotion and education: a systematic review - Wahyuningsih, Ida; Hanindriyo, Lisdrianto; Widiati, Sri (Padjadjaran Journal of Dentistry, 2026)
Introduction: Augmented reality (AR) is an innovative technology being increasingly utilized in oral health promotion and education. This systematic review aimed to map and describe the types of augmented reality interventions, target populations, outcomes, and implementation challenges in oral health promotion and education. Methods: This systematic review was conducted in accordance with PRISMA-ScR guidelines. A systematic literature search was performed across Google Scholar, ScienceDirect, and PubMed, to identify articles published between 2020 and 2024. Studies were included based on predefined criteria focusing on augmented reality interventions for oral health promotion and education. Exclusion criteria comprised review articles, editorials, commentaries, and studies without full-text availability. Study selection was conducted independently by two reviewers. Results: A total of 456 articles were identified, of which nine studies met the inclusion criteria. Most studies targeted children (55.5%) and used non-randomized designs (77.8%). Augmented Reality interventions included smart toothbrushes, serious games, and mobile applications. Overall, these interventions improved oral health knowledge, motivation, oral hygiene status, and brushing skills. Conclusion: This systematic review underscores the potential of AR as an innovative tool in oral health education. AR interventions have shown effectiveness in improving knowledge, motivation, self-efficacy, and health behaviors across diverse populations, particularly among children and vulnerable groups. However, while the findings are promising, limitations related to study design, sample sizes, and intervention durations necessitate further research.